2019
DOI: 10.1155/2019/7405602
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 Protects against High Glucose-Induced Cell Injury in Human Umbilical Vein Endothelial Cells

Abstract: Aims. Inflammation was closely associated with diabetes-related endothelial dysfunction. C1q/tumor necrosis factor-related protein 3 (CTRP3) is a member of the CTRP family and can provide cardioprotection in many cardiovascular diseases via suppressing the production of inflammatory factors. However, the role of CTRP3 in high glucose- (HG-) related endothelial dysfunction remains unclear. This study evaluates the effects of CTRP3 on HG-induced cell inflammation and apoptosis. Materials and Methods. To prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…According to the previous studies, CTRP3 executed its roles via multiple mechanisms, such as regulation of p38 MAPK, 24 c-Jun NH-terminal kinase (JNK), 24 extracellular signal-regulated kinase (ERK1/2), 25 Nrf2/HO-1, 20 AKT/mTOR, 26 Notch, 27 and AMPK. 19 Among these signaling pathways, AMPK is a heterotrimeric complex that plays an important role in maintaining energy homeostasis in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous studies, CTRP3 executed its roles via multiple mechanisms, such as regulation of p38 MAPK, 24 c-Jun NH-terminal kinase (JNK), 24 extracellular signal-regulated kinase (ERK1/2), 25 Nrf2/HO-1, 20 AKT/mTOR, 26 Notch, 27 and AMPK. 19 Among these signaling pathways, AMPK is a heterotrimeric complex that plays an important role in maintaining energy homeostasis in eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…19 In addition, there were several studies indicating the antiapoptotic effects of CTRP3 on HUVECs and mouse aortic endothelial cells stimulated with oxidized low-density lipoprotein (ox-LDL) 19 or high glucose. 20 However, there are little data regarding the role of CTRP3 in endothelial injury induced by high uric acid. Our study showed that, for rats with hyperuricemia, CTRP3 increased eNOS mRNA expression in the thoracic aortas.…”
Section: Discussionmentioning
confidence: 99%
“…CTRP3 is a most well‐studied member of CTRP family that has been found to closely related with diabetes mellitus and diabetic complications . CTRP3 exerts protective effect on diabetes‐related endothelial dysfunction via protecting human umbilical vein endothelial cells (HUVECs) from HG‐induced cell injury . CTRP3 inhibits HG‐induced oxidative stress and apoptosis in retinal pigment epithelial (RPE) cells, suggesting that CTRP3 may be a therapeutic target for the treatment of diabetic retinopathy .…”
Section: Discussionmentioning
confidence: 99%